2022
DOI: 10.1016/j.joca.2021.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of GLPG1972/S201086, a potent and selective small-molecule inhibitor of ADAMTS5

Abstract: Objective: A disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS5) is a key enzyme in degradation of cartilage in osteoarthritis (OA). We report the pharmacological characterization of GLPG1972/S201086, a new, potent and selective small-molecule ADAMTS5 inhibitor. Methods: Potency and selectivity of GLPG1972/S201086 for ADAMTS5 were determined using fluorescently-labeled peptide substrates. Inhibitory effects of GLPG1972/S201086 on interleukin-1a-stimulated glycosaminoglycan release in mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
0
21
1
Order By: Relevance
“…22 Furthermore, GLPG1972 significantly reduced femorotibial cartilage proteoglycan loss, cartilage damage, and subchondral bone sclerosis in a mouse model of OA (ie, destabilization of the medial meniscus). 22 Early in vitro testing suggested that GLPG1972 is a potential cytochrome P450 (CYP) 3A4 inducer, a potential substrate of CYP3A4, and to a lesser extent of CYP2D6. Based on these in vitro results, 2 in vivo drug-drug interaction studies were conducted.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…22 Furthermore, GLPG1972 significantly reduced femorotibial cartilage proteoglycan loss, cartilage damage, and subchondral bone sclerosis in a mouse model of OA (ie, destabilization of the medial meniscus). 22 Early in vitro testing suggested that GLPG1972 is a potential cytochrome P450 (CYP) 3A4 inducer, a potential substrate of CYP3A4, and to a lesser extent of CYP2D6. Based on these in vitro results, 2 in vivo drug-drug interaction studies were conducted.…”
mentioning
confidence: 96%
“… 22 Furthermore, GLPG1972 significantly reduced femorotibial cartilage proteoglycan loss, cartilage damage, and subchondral bone sclerosis in a mouse model of OA (ie, destabilization of the medial meniscus). 22 …”
mentioning
confidence: 96%
See 3 more Smart Citations